The Evolution of Small-RNA-Mediated Silencing of an Invading Transposable Element. (25th September 2018) - Kelleher, Erin S; Azevedo, Ricardo B R; Zheng, Yichen
Abstract: Transposable elements (TEs) are genomic parasites that impose fitness costs on their hosts by producing deleterious mutations and disrupting gametogenesis. Host genomes avoid these costs by regulating TE activity, particularly in germline cells where new insertions are heritable and TEs are exceptionally active. However, the capacity of different TE-associated fitness costs to select for repression in the host, and the role of selection in the evolution of TE regulation more generally remain controversial. In this study, we use forward, individual-based simulations to examine the evolution of small-RNA-mediated TE regulation, a conserved mechanism for TE repression that is employed by both prokaryotes and eukaryotes. To design and parameterize a biologically realistic model, we drew on an extensive survey of empirical studies of the transposition and regulation of P -element DNA transposons in Drosophila melanogaster . We observed that even under conservative assumptions, where small-RNA-mediated regulation reduces transposition only, repression evolves rapidly and adaptively after the genome is invaded by a new TE in simulated populations. We further show that the spread of repressor alleles through simulated populations is greatly enhanced by two additional TE-imposed fitness costs: dysgenic sterility and ectopic recombination. Finally, we demonstrate that the adaptive mutation rate to repression is a critical parameter that influences both the evolutionary trajectory of host repression and the associated proliferation of TEs after invasion in simulated populations. Our findings suggest that adaptive evolution of TE regulation may be stronger and more prevalent than previously appreciated, and provide a framework for interpreting empirical data.